The Effectiveness of The Implementation of Sharia Principles in the Digital Banking Industry - Hasanudin, Hasanudin; Rijal Anshori, Arif; Setiawan, Iwan; Alputri, Misella (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
Education on the importance of Sharia principles and the benefits of Islamic banking must be increased so that people better understand and choose Islamic banking services. Increasing financial literacy and awareness of Islamic banking products helps drive wider adoption in society. This study aims to elaborate on the effectiveness of the application of sharia principles in the digital banking industry. The research method used is library research with a qualitative approach. The results of the study show that adhering to Sharia principles, the Sharia digital banking industry not only offers an ethical alternative to Islamic law but also provides modern and efficient services to customers. Sharia-based digital banking is expected to increase financial inclusion and provide wider access to the public to use financial services by Sharia principles. The effectiveness of the implementation of sharia principles in the digital banking industry is generally positive, with many benefits that can be felt by customers and the financial industry as a whole. However, challenges in terms of technology, regulation, and digital literacy need to continue to be addressed to ensure sustainable and inclusive growth.